Government Support and Firm Profitability in Vietnam - Thanh Minh Nguyen; Tuyen Quang Tran; Long Thanh Do (Comparative Economic Research. Central and Eastern Europe, 2018)
Existing studies on the linkage between government subsidies and firm financial performance often use a mean regression approach and focus mainly on developed countries. To fill the gap, this study, for the first time, considers the impact of government support activities on the profitability of manufacturing SMEs in a developing country, Vietnam. Using an unbalanced panel dataset covering the period 2009-2015, government financial supports show an insignificant linkage with firm profitability when using OLS. However, a fixed-effect quantile approach reveals that government financial support is negatively related for firms with low profit but is positively related for firms in the high profitability percentile. Our findings also suggest that policymakers should focus on helping start-ups instead of ineffective, informal firms.
Keywords: C21; C23; D22; D25; 330; government support; profitability; quantile approach; SMEs